2015
DOI: 10.1097/sap.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Nipple-Sparing Mastectomy via an Inframammary Fold Incision for Patients With Scarring From Prior Lumpectomy

Abstract: Patients with scarring from prior lumpectomy do not have a higher rate of NAC ischemia and may be considered for NSM via an IMF incision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…In an evaluation of NSM via IMF in patients with previous lumpectomy, Huston et al (2015) demonstrated an overall rate of 20.4% NAC ischemia. Conversely, they found no significant correlation between the incidence of NAC ischemia and various demographic and clinical factors including age, BMI, resection volume, prior radiation, ADM use, diabetes, or smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…In an evaluation of NSM via IMF in patients with previous lumpectomy, Huston et al (2015) demonstrated an overall rate of 20.4% NAC ischemia. Conversely, they found no significant correlation between the incidence of NAC ischemia and various demographic and clinical factors including age, BMI, resection volume, prior radiation, ADM use, diabetes, or smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…This incision may be better for patients with smaller, less ptotic breasts, as those with larger, more ptotic breasts are at an increased risk for nipple malposition [29]. However, surgeons have reported successful results in patients with medium and large breasts with more ptosis [27].…”
Section: Inframammary Fold Incisionmentioning
confidence: 99%
“…The incision leaves no visible scar on the anterior surface of the breast mound, hiding it within the natural crease of the breast, all while providing great exposure for tumor resection. Also, there is decreased risk of lateralization of the nipple with the use [29], and it can be used for any future breast surgeries if the inferior skin is conserved.…”
Section: Inframammary Fold Incisionmentioning
confidence: 99%
“…The emerging trend, especially in prophylactic mastectomies is to retain native nipple and areolar tissue 26 with intraoperative sampling of subareolar region to ensure absence of malignant cells. 27 The clinical rationale for keeping native tissue relates to the easy palpation of potential abnormalities in the periareolar region, with visual review of long-term imaging of the nipple/areolar complex. 26 Prophylactic contralateral mastectomy is a common request from patients who require a mastectomy on the affected side, or in lieu of breastconserving surgery.…”
Section: Prophylactic Mastectomymentioning
confidence: 99%
“…Skin-sparing mastectomy is common, especially if immediate or delayed reconstructive surgery is planned. 27 Negative suction devices are inserted at wound closure to drain excess serosanguinous fluids. Drains remain until the 24-hour output is approaching 30 cc or less.…”
Section: Mastectomymentioning
confidence: 99%